6-BENZILADENINE (BA) AND GIBERELIC ACID (GA3 ) EFFECTS ON in vitro DEVELOPMENT OF Selenicereus grandiflorus (L.) BRITTON & ROSE (CACTACEAE) - FONTES ESTEVES, PATRÍCIA; SATO, ALICE; ESQUIBEL, MARIA APPARECIDA (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
Stem segments of Selenicereus grandiflorus (L.) Britton & Rose were cultured on MS medium supplemented with different concentrations of 6-benziladenine (BA) and gibberelic acid (GA3 ) with the objective to investigate the effects on plant organogenesis and rhizogenesis. Cultures treated with BA in concentrations of 0.22 or 0.88 mM, induced mean production of 9 and 10 shoots/explant in 29.0 and 32.3% of explants, respectively in 30 days of culture; while in 75 days of culture, 58.1 and 48.4% of explants developmented 28 and 21 shoots/ explant. Regenerated shoots rooted within 30 days of culture in 100% of explants. The treatment with GA3 at 0.29 or 0.88 mM, induced mean production of 9 and 5 shoots/explant with shoots percentage of 19.6 and 9.5, respectively, in 30 days of culture. However in 75 days of culture, the addition of GA3 did not produce effect on shoots production. The application of GA3 did not induce significant effect on roots development, besides inhibited its elongation.